Pemanfaatan Limbah Bambu untuk Mainan Musik Prasekolah dengan Pendekatan Surface Mimicry - Joyodiharjo, Bismo Jelantik; Sidarta, Nabilla Puteri; Piliang, Yasraf Amir; Larasati, Dwinita; Syamsudin, Tati Suryati (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2024)
During design process, Surface Mimicry can be used as an alternative approach by utilizing the role and similarity of objects based on their familiarity with shapes. Unlike behavior and functional mimicry, the point of view on surface mimicry expresses the visual similarity of objects rather than their actions and functions. Bamboo is a traditional Indonesian material that is easy to find and use as a basic material for various musical instruments, but the waste is still rarely processed. For example, at the location of Saung Angklung Udjo's partner as a supplier of angklung in large quantities in West Java, waste from production with a subtractive process of bamboo sticks of various sizes ends up being material that is only burned. This article tells the design process of prototype works of preschool music toys that utilize the potential of bamboo waste and the subtractive production process through a surface mimicry approach that is relevant to the character of the original material form. This design exploration activity is part of mimicry research (surface, behavior, function), process (formative, subtractive, additive) and system (integral, modular) which can be an alternative method in developing innovative products in the context of environmentally friendly and sustainable design.